2021
DOI: 10.1007/s11695-021-05499-3
|View full text |Cite
|
Sign up to set email alerts
|

Is One Anastomosis Gastric Bypass with a Biliopancreatic Limb of 150 cm Effective in the Treatment of People with Severe Obesity with BMI > 50?

Abstract: Purpose The treatment of people with severe obesity and BMI > 50 kg/m2 is challenging. The present study aims to evaluate the short and mid-term outcomes of one anastomosis gastric bypass (OAGB) with a biliopancreatic limb of 150 cm as a primary bariatric procedure to treat those people in a referral center for bariatric surgery. Material and Methods Data of patients who underwent OAGB for severe obesity with BMI > 50 kg/m2 between 2010 and 2017 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 39 publications
(52 reference statements)
2
2
0
Order By: Relevance
“…Our study also showed the efficacy of OAGB in remission of obesity associated medical problems including T2DM, DLP, HTN, OSA and GERD in 94.2%, 72.9%, 90.9%, 100% and 91.6% of patients with BMI ≥ 50 kg/m 2 respectively. Liagre et al 7 showed evolution of T2DM, DLP, HTN and OSA after OAGB in 92%, 98%, 76% and 97% of patients with BMI ≥ 50 kg/m 2 respectively that were nearly similar to our findings. Although the efficacy of OAGB in remission of T2DM was as the same as SG in some studies 6 , 22 , 23 , OAGB has significant superiority in remission of other obesity associated medical problems in patients with BMI ≥ 50 kg/m2.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our study also showed the efficacy of OAGB in remission of obesity associated medical problems including T2DM, DLP, HTN, OSA and GERD in 94.2%, 72.9%, 90.9%, 100% and 91.6% of patients with BMI ≥ 50 kg/m 2 respectively. Liagre et al 7 showed evolution of T2DM, DLP, HTN and OSA after OAGB in 92%, 98%, 76% and 97% of patients with BMI ≥ 50 kg/m 2 respectively that were nearly similar to our findings. Although the efficacy of OAGB in remission of T2DM was as the same as SG in some studies 6 , 22 , 23 , OAGB has significant superiority in remission of other obesity associated medical problems in patients with BMI ≥ 50 kg/m2.…”
Section: Discussionsupporting
confidence: 91%
“…Liagre et al 7 in a study on 245 patients with BMI ≥ 50 kg/m 2 who underwent OAGB with a BPL of 150 cm, showed that OAGB is an effective method with low complication rates(5.7%) and no mortality. In their study, only 0.8% of patients needed to be underwent for second bariatric procedure due to weight loss failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our experience of OAGB with a constant biliary loop of 150 cm in patients with BMI > 50 showed results comparable to those published by Eskandaros [2]. It has been demonstrated that the increase of the biliary loop dangerously increases the risk of malnutrition by decreasing the total alimentary limb length (TALL) [3,4].…”
supporting
confidence: 84%